1999
DOI: 10.1002/(sici)1099-1085(19990228)13:3<401::aid-hyp746>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater and fish—insights from northern North America

Abstract: Fishes inhabiting streams and rivers in the interior of North America experience a continental climate. Water temperatures reach 0 °C in winter and are high in summer. There is a marked seasonal cycle in discharge. These circumstances make groundwater a crucial component of river habitats. Groundwater can influence the distribution, reproductive success, biomass and productivity, behaviour and movements of fishes, and is especially important in winter and summer. Winter flows are minimal and are affected by ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(66 citation statements)
references
References 53 publications
3
63
0
Order By: Relevance
“…Deeper winter snowpack also maintains taliks, or unfrozen areas, in lake and river beds that permit linkages between surface and groundwater flows during winter (Prowse, 1990;Allan, 1995). Increased groundwater flows improve winter refugia by expanding the volume of available habitat (Power & Barton, 1987;Power et al, 1999) and can increase water temperatures (Allan, 1995). Although little is known about the exact role of temperature in determining the overwinter condition of salmonids, Elliott (1994) has shown that the proportion of daily energy use available for growth and metabolism in brown trout Salmo trutta L., increases slightly with temperature at the lower end (3-5 C) of the thermal niche.…”
Section: Age-at-catch Modelmentioning
confidence: 99%
“…Deeper winter snowpack also maintains taliks, or unfrozen areas, in lake and river beds that permit linkages between surface and groundwater flows during winter (Prowse, 1990;Allan, 1995). Increased groundwater flows improve winter refugia by expanding the volume of available habitat (Power & Barton, 1987;Power et al, 1999) and can increase water temperatures (Allan, 1995). Although little is known about the exact role of temperature in determining the overwinter condition of salmonids, Elliott (1994) has shown that the proportion of daily energy use available for growth and metabolism in brown trout Salmo trutta L., increases slightly with temperature at the lower end (3-5 C) of the thermal niche.…”
Section: Age-at-catch Modelmentioning
confidence: 99%
“…In our study, Columbia Slimy Sculpin occurred in the coldest reaches, where maximum water temperatures rarely or never reached 22uC, even during the record warm summer of 2007. Rocky Mountain Sculpin tolerated warmer temperatures, including maximum temperatures exceeding 23uC in four reaches and as high as 27.5uC in one reach; however, the fish may have retreated to cooler groundwater-influenced patches in the substrate during very high temperatures (Power et al, 1999). Similarly, Uranidea cognata generally inhabits colder streams, deeper lake habitats, and occurs farther north compared to U. bairdii (Scott and Crossman, 1973;Hubbs et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Lolo Creek, about 3 km upstream of the mouth, August water temperature averaged 15.8uC over four summers -1999Chris Clancy, Montana Fish, Wildlife, and Parks, unpubl. data), and in O'Brien Creek, mean August temperature in 2007 was 16.6uC (Adams et al, 2015:table 3).…”
Section: Discussionmentioning
confidence: 99%
“…At a coarse spatial scale, groundwater can influence the distribution and abundance of aquatic organisms [23], [24] and reduce the occurrence of temperature fluctuations that may result in reproductive failure of certain species [25]. At fine spatial scales, some fishes show behavioral responses to thermal refuges by selecting spawning locations [26], [27], avoiding ice break up and frazil ice [28], or thermoregulating by occupying groundwater influenced areas during warm or cool water periods [16], [19], [20], [29].…”
Section: Introductionmentioning
confidence: 99%